Constructive Alignment of Higher Education Curricula: The Case of a Philippine State University (Asia Pacific Journal of Social and Behavioral Sciences, 2022)
Constructive alignment is an approach to outcome-based education that involves examining curriculum, discipline, and/or course level initiatives. This research sought to assess the match among the institutional outcomes, program outcomes, performance indicators, assessment, evaluation methods, and standards in 20 undergraduate curricula. The researchers mainly used qualitative research methods like document analysis, curriculum mapping, and online focused group discussion. Findings revealed that there was a high alignment of the curricula in the university. This means that five out of six dimensions components were constructively aligned. During the focus group discussion, the participants underscored the significance of using the institution’s vision, mission, and goals as anchorage in crafting the institutional outcomes. Additionally, majority of the participants highlighted that they based their performance indicators on CHED’s policies, standards and guidelines. Regarding the participants’ experiences in aligning their performance indicators and assessment methods, the programs’ syllabi were valuable in determining their assessment methods for their performance indicators. One difficulty though was delineating between assessment and evaluation since both denote processes of learning measurement. However, while the former entails appraising a student’s level of performance, the latter involves gauging the degree to which outcomes are attained based on a set of standards. In terms of the outcomes’ relevance to 21st century learning, they were found to be relevant to most of the seven cluster competencies except for computing technology, which is given the least attention in higher education curricula. Since there is a high constructive curriculum alignment in the university, it is therefore concluded that the five elements of the curriculum, namely, the institutional outcomes (with the vision and mission as anchorage), program outcomes unique to a particular specialization, performance indicators, assessment, and standards are highly coherent except for the evaluation methods. It is recommended that evaluation method shall be continually calibrated to ensure its coherence with the other dimensions and that computing technology shall be mainstreamed in the curricula across all programs.
Keywords: Constructive alignment, institutional outcomes, program outcomes, performance indicators, assessment, evaluation methods, standards